Poverty, corruption, trade, or terrorism? Strategic framing in the politics of UK anti-bribery compliance. (February 2017) - Gutterman, Ellen
What explains longstanding UK non-compliance with international anti-bribery norms? Drawing on evidence from a comparative study of state compliance with the Organization for Economic Cooperation and Development (OECD) anti-bribery Convention and building on the literature on 'framing' in Sociology and International Relations, this article identifies and illustrates the impact of strategic policy framing on UK anti-bribery policy in the years following the United Kingdom's commitment to criminalize transnational business bribes, in 1997. The research examines the way in which anti-bribery proponents and opponents framed the practice of transnational bribery differently across four distinct policy contexts in the United Kingdom: international development and poverty reduction, domestic anti-corruption, strategic trade, and—following 11 September 2001—international anti-terrorism. The analysis shows that: (a) policy advocates' choice of frame crucially affected the timing and scope of UK anti-bribery legislation and the extent of UK (non)compliance with international anti-corruption law; and (b) the expedient frame was not necessarily the most conducive to full compliance.